Measuring Relative Cue Strength as a Means of Validating an Inventory of Expert Offender Profiling Cues. (June 2013) - Morrison, Ben W.; Wiggins, Mark W.; Bond, Nigel W.; Tyler, Michael D.
Cues have been identified as important precursors to successful diagnoses among expert practitioners. However, current approaches to the identification of expert cues typically rely on subjective methods, making the validity of cues difficult to establish. The present research examined the utility of a Paired-Concept Association Task (P-CAT) as a basis for discriminating expert and novice cue activation in the context of offender profiling. Three studies are reported: 1A employed a cognitive interview for the acquisition of cue-based concepts used by experts and novices; 1B presented pairs of concepts as part of the P-CAT, which recorded response latency; and, 1C employed a survey to further gauge participants' perceptions of the concepts. The results revealed differences between experts and novices in the cue-based associations activated, and in the response latencies associated with the P-CAT, across expertise. The P-CAT accurately discriminated expert from novice cue activation and consequently offers a new method for objectively validating expert cue use.